PENGARUH SARANA PRASARANA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG PERPUSTAKAAN DAERAH KABUPATEN BINTAN - Firda Rahmadani, Aulia; Jintar, Catri; Deryane, Imalinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of enhancing visitor satisfaction at the Bintan Regency Regional Library through the provision of adequate facilities and optimal service quality. Although the library has undergone renovations that improved physical comfort and increased visitor numbers, several issues persist, such as suboptimal collection arrangement, limited holdings in certain subject areas, and service that is not yet fully proactive. This study aims to analyze the influence of facilities and service quality on visitor satisfaction at the Bintan Regency Regional Library, both partially and simultaneously. A quantitative method with an associative approach was employed. Sampling was conducted using a non-probability purposive sampling technique, involving 164 respondents who had visited and utilized the library's services. Data were collected via questionnaires and analyzed using multiple linear regression, preceded by data quality and classical assumption tests. The results indicate that facilities have a positive and significant effect on visitor satisfaction, with a significance value of <0.001 and a calculated t-value of 17.153. Service quality also has a positive and significant effect on visitor satisfaction, with a significance value of <0.001 and a calculated t-value of 16.460. Simultaneously, facilities and service quality exert a positive and significant influence on visitor satisfaction, with a significance value of <0.001 and a calculated F-value of 309.048. The findings demonstrate that improving the quality of facilities and services provided by the library can significantly enhance visitor satisfaction.